If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(4 + 9x) = 3(x + -1) (4 * -8 + 9x * -8) = 3(x + -1) (-32 + -72x) = 3(x + -1) Reorder the terms: -32 + -72x = 3(-1 + x) -32 + -72x = (-1 * 3 + x * 3) -32 + -72x = (-3 + 3x) Solving -32 + -72x = -3 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -32 + -72x + -3x = -3 + 3x + -3x Combine like terms: -72x + -3x = -75x -32 + -75x = -3 + 3x + -3x Combine like terms: 3x + -3x = 0 -32 + -75x = -3 + 0 -32 + -75x = -3 Add '32' to each side of the equation. -32 + 32 + -75x = -3 + 32 Combine like terms: -32 + 32 = 0 0 + -75x = -3 + 32 -75x = -3 + 32 Combine like terms: -3 + 32 = 29 -75x = 29 Divide each side by '-75'. x = -0.3866666667 Simplifying x = -0.3866666667
| 25t+30b=750 | | 3x+1=1-3x | | -60+40x=20x | | (t)+2.7=4.5 | | -7(y-2)=-2y+39 | | 6(k-7)-(8+9k)=-4k | | 8n-3(5)= | | x^2+4x=5x | | -2x+21=7x-15 | | 8(2x-4)+5(3x+6)=29 | | (2x+28)(4x+10)= | | -3x+1=-2(3x+10) | | 2w^2+2w=34 | | 5r+15=2.25r | | 3(6+x)=30 | | 3x+4-2-x=14 | | -3(e+4)=4w-5 | | -3+2x=-x-6 | | 1-6x=5-4x | | 22-44= | | 13x+9=-15 | | 2a+4.2=3a-16 | | 2y+4=26 | | XY=98 | | 12p=-4 | | -6n+7n+4= | | 5k+8(k-4)=-84 | | 4x-7=x-34 | | 5y-5=7y+9+10y+4 | | -11=1+8k | | k*(-9k)*k=0 | | X(3x-5)=(3x+8)(x-5) |